STRATEGI IMPLEMENTASI PROGRAM DINIYAH DAN IMPLIKASI DALAM PENINGKATAN SEMANGAT BELAJAR DI SEKOLAH IT FAJAR HIDAYAH ACEH BESAR - Khairiah Yonas, Elvi (PENCERAHAN, 2023)
Strategy in education refers to the approach chosen and implemented to achieve educational goals. This involves selecting appropriate methods, techniques, and resources to teach, guide, and develop students. These strategies can cover various aspects of education, including curriculum, instruction, assessment, classroom management, and teacher professional development. This research was conducted to describe the application of the diniyah program in increasing the enthusiasm for learning held by students at the Fajar Hidayah IT School, Aceh Besar, which includes motivation for the material, the will to continue learning despite experiencing difficulties, awareness of clear learning goals. This research is in qualitative form, where this approach aims to look at a process of educational activities based on what happens in the field. The instruments used to collect data are interviews, observation and documentation. Based on the results of interviews and observations, researchers found that the implementation of the diniyah program had a positive effect on students' enthusiasm for learning, starting from understanding the material, students' awareness of learning and students starting to apply the knowledge they had learned in their daily lives.